Appréhender le risque médicamenteux dans la relation médecin-malade : expériences et stratégies profanes de personnes souffrant de maladie chronique en France - Ashley Ouvrier (Anthropologie & Santé)
This anthropological study documents the way people living with chronic diseases in France come to grips with pharmaceutical risks while they interact with their general practitioner or specialist. Based on 25 qualitative interviews among people suffering from chronic disease, the research shows how patients feel concerned about pharmaceutical risks but have trouble objectivizing their specific fears with their medical practitioner (iatrogenic conditions, side effects, drug interactions), leading to irregular medicine taking. The patient-doctor communication on pharmaceutical risks appears to be an inter-subjective experience only when patients have a high socio-cultural background or when they are supported by physicians aware of the pharmaceutical risk issues and ready to help them face other physicians’ paternalistic behavior